Transit-Oriented Development and urban ecological transition: limits of application to Brazilian cities - Di Biase , Luca (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – Analyze the potential that the urban planning approach called Transportation Oriented Development (TOD) has to change the trajectory of unsustainability of urban dynamics in contexts such as Brazil, as well as its limits, considering the challenges that the climate-environmental crisis poses to cities. Methodology – Review of national and international literature on the main experiences of Transport Oriented Development. Originality/Relevance – Currently, there are no studies that analyze the potential and limits of the DOT approach to promote an ecological transition of the urban development model based on the specificities of the urbanization process in Brazil and its dynamics consolidated within the scope of planning. Results – The analysis carried out points to a substantial ineffectiveness of the TOD approach in terms of sustainability and resilience when applied in the local context, while at the same time identifying the full and effective participation of civil society in the decision-making process as the path to be followed to enable a real change in the urban development model compatible with the preservation of natural ecosystems and mitigation of the effects of climate change. Theoretical/Methodological Contributions – The study carried out presents as its main theoretical/methodological implication for the ecological transition of cities, the need to formulate urban policies designed based on the specificities that the local context presents, which are not simply imported from countries characterized by different historical, social and economic dynamics to be successively adapted, identifying in the creation of truly representative participation mechanisms the necessary condition to achieve this objective. Social and Environmental Contributions – The study highlights the limits that current urban policies implemented in Brazilian cities present in terms of a real reduction in anthropogenic impacts on natural ecosystems and the climate, bringing to light the relationship that exists between transparent and democratic decision-making processes and a change in the urban development model that makes cities more socially just and environmentally sustainable possible.